Why MENA Needs a Finance and Private Sector Marshall Plan - Ridenour, Stefanie (World Bank, Washington, DC, 2014)
Middle East and North Africa (MENA) is a largely middle income (MIC) region however, it tends to perform more like a low income (LIC) region on many critical financial and private sector economic indicators. This is an important explanatory variable as to why MENA job growth is so weak. This brief provides an overview of a series of areas where MENA lags behind other regions, particularly LIC regions such as Sub-Saharan Africa and South Asia. More than ever, World Bank support is needed to create jobs and boost shared prosperity in a promising region which significantly underperforms.